Determinants of occurrence of chronic hypertension in patients who had preeclampsia at the Yaoundé central hospital - Cyrille, Noa Ndoua Claude; Linda, Basseck; Nadège, Nganou Chris; Madye, Ngo Ndingom; Junie, Metogo Ntsama; Esapebong, Maryanne N.; Florent, Fouelifack Ymele (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is an abnormal elevation of blood pressure with systolic blood pressure ≥140 mmHg, and/or diastolic blood pressure ≥90 mmHg associated with proteinuria in a pregnant woman beyond 20 weeks of gestation. This generally disappears postpartum. Some women, however, will later on develop chronic hypertension. Our objective was to assess the determinants of occurrence of chronic hypertension in patients who had preeclampsia at the Yaoundé Central Hospital. Methods: we carried out a retrospective case-control study over ten years from January 2012 to December 2022. The cases consisted of women who developed chronic hypertension within 5 years following an episode of preeclampsia in pregnancy. These were matched with two controls each; women who had not developed chronic hypertension following preeclampsia in pregnancy. Results: We recruited 60 cases and 120 controls. After bivariate analysis, the sociodemographic factors seemingly associated with the occurrence of chronic hypertension were; age between 25-35 years p=0.01; OR=2.9 (1.5-5.5), the profession of pupil/student; p=0.05; OR=0.3 (0.12-0.7). The clinical factors found were multigravidas; OR=3.1 (1.6-5.9); p=0.00, as well as pauciparous women; OR=2.1 (1.1-4.4); p=0.03, family history of hypertension; OR=2.5 (1.3-4.8); p=0.04 and BMI greater than 40 kg/m2; OR=3.8 (1.0-13.6); p=0.02. After logistic regression, the factor independently associated with the occurrence of chronic hypertension is a family history of hypertension; p=0.01; OR=2.45 (1.18-4.96). Conclusions: A family history of hypertension is a major risk factor for the occurrence of chronic hypertension in patients who have had preeclampsia.